2011
DOI: 10.1007/s10029-011-0808-y
|View full text |Cite
|
Sign up to set email alerts
|

Five-year results of a randomised controlled multi-centre study comparing heavy-weight knitted versus low-weight, non-woven polypropylene implants in Lichtenstein hernioplasty

Abstract: BackgroundThis prospective randomised study evaluated whether non-knitted and non-woven lightweight implants can influence postoperative pain and time of return to normal activity, without increasing the recurrence rate in Lichtenstein inguinal hernioplasty.MethodsPatients were operated on in four centres, randomised blindly into two groups with respect to the mesh used: Surgimesh WN (non-woven polypropylene microfibre sheet) and heavy weight polypropylene mesh. The operation was performed according to the Lic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 14 publications
0
29
1
Order By: Relevance
“…foreign body sensation and chronic pain are reduced. Patients report less consumption of analgesics at the early postoperative period, quicker ambulation and return to work [10].…”
Section: Polypropylene Implantsmentioning
confidence: 99%
“…foreign body sensation and chronic pain are reduced. Patients report less consumption of analgesics at the early postoperative period, quicker ambulation and return to work [10].…”
Section: Polypropylene Implantsmentioning
confidence: 99%
“…However, among these studies, 33 different validated instruments were identified (tables 4, 5, 6) [11,13,14,17,19,21,26,28,29,32,36,38,41,43,45,47,48,51,53,56,57,58,59,60,61,62,63,64,65,79,90]. …”
Section: Resultsmentioning
confidence: 99%
“…First, there was heterogeneity in the postoperative time period after which pain was classified as chronic. This ‘chronic' time frame ranged between 1 and 36 months [63,64,65,66,67]. Second, some studies included the quantitative factor PI in their definition of CPIP, which was either expressed using descriptive terms [68,69,70,71,72,73,74,75], a visual analog scale (VAS) score, or a QOL score [31,76,77,78,79,80,81,82,83,84,85].…”
Section: Resultsmentioning
confidence: 99%
“…Tension-free repair with non-absorbable mesh (polypropylene) has been used in a higher number of cases during the past few years. 4 When meshes are categorized by density, a mesh with density >100g/m 2 is accepted as heavy, whereas a 35-50g/m 2 density is classified as lightweight. Several recent controlled clinical studies have suggested that lightweight meshes may improve patient comfort.…”
Section: Introductionmentioning
confidence: 99%